(untitled) (Journal of Universal Science Research, 2025)
This article provides an overview of the major classifications of phraseological units (PUs) in the English language, exploring different criteria such as semantic motivation, structural properties, and functional characteristics. It examines the contributions of prominent linguists like Vinogradov, Kunin, and Gläser, highlighting their respective approaches to categorizing idioms and fixed expressions. The article aims to provide a comprehensive understanding of the complexities inherent in phraseology and its crucial role in enriching communication.